Anticancer properties of krill oil - BAKIRHAN, YUNUS EMRE (My University, 2019)
Krill which is a shrimp-like cold ocean creature is an important nutraceutical agent because it contains nutrient components (polyunsaturated fatty acids, astaxanthin, etc.) that have positive effects on health. Although its cardioprotective, neuroprotective and anti-inflammatory properties have been emphasized so far, it also has anticancer properties. It has been reported to inhibit the proliferation of cancerous cells, prevent metastasis and tumor growth, and induce apoptosis in cancer cells through various mechanisms such as regulation of the omega-3/omega-6 ratio, inhibition of reactive oxygen species (ROS) formation, activation of caspase 3/9, and increasing mitochondrial membrane potential. It has been reported to induce apoptosis as well. It is believed that Krill can reduce the incidence of cancer and play an effective role in cancer treatment due to the above-mentioned properties.
Keywords: Sağlık Bilimleri; Beslenme ve Dietetik; Health Sciences; Nutrition and Dietetics; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Tarım Bilimleri; BESLENME VE DİYETETİK; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); AGRICULTURAL SCIENCES; NUTRITION & DIETETICS; Beslenme ve Diyetetik